2019
DOI: 10.5603/pjnns.a2019.0033
|View full text |Cite
|
Sign up to set email alerts
|

Multiple sclerosis: oral health, behaviours and limitations of daily oral hygiene — a questionnaire study

Abstract: clinical rationale for the study. Neurological deficits and progressing disability in patients with multiple sclerosis (MS) may hamper daily oral hygiene, but their relations with oral problems have not yet been clearly determined. Aim of the study. The aim of this study was to identify the most significant dental problems and limitations of daily oral hygiene in Polish patients with MS. Material and methods. 199 patients with diagnosed MS (median age 37 years) treated in the neurological outpatient clinic wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…What is more, identifying impairments in autonomic arousal might be further aggravated by a generally reduced response in older participants [ 50 ]. However, an absent correlation between SCR and age in our stroke cohort could reflect impaired autonomic arousal and was also reported in previous work on stroke patients [ 56 ]. Looking at individual values showed that a null correlation was primarily driven by lowered SCR amplitudes in the younger patients of our sample compared to HCs of a similar age.…”
Section: Discussionsupporting
confidence: 73%
“…What is more, identifying impairments in autonomic arousal might be further aggravated by a generally reduced response in older participants [ 50 ]. However, an absent correlation between SCR and age in our stroke cohort could reflect impaired autonomic arousal and was also reported in previous work on stroke patients [ 56 ]. Looking at individual values showed that a null correlation was primarily driven by lowered SCR amplitudes in the younger patients of our sample compared to HCs of a similar age.…”
Section: Discussionsupporting
confidence: 73%
“…Clinical symptoms of MS include motor deficits, vision deficits, bulbar symptoms, cognitive dysfunctions, and mental disturbances, which might interfere with oral hygiene. Furthermore, the progressively increasing functional disability, in association with the drugs used for MS, can cause a greater incidence of pathologies in the mouth and teeth [15].…”
Section: Discussionmentioning
confidence: 99%
“…The autonomic nervous system that acts as an unconscious control of respiration, cardiac regulation, vasomotor activity, and some reflexive actions has been shown to be dysfunctional in a subset of patients with epilepsy. 19 The sympathetic division of the autonomic nervous system is involved in the well-known fight or flight response. A study that investigated the sympathetic response to HV by looking at heart rate responses found that patients with mesial temporal lobe epilepsy showed increased sympathetic responses to HV compared to healthy subjects.…”
Section: Dysfunction Of the Autonomic Nervous Systemmentioning
confidence: 99%